The Influence Of Perceived Usability, Convenience And Security On Generation Z's Interest In Using Islamic Mobile Banking With Trust As An Intervening Variable - Ika Yuni Rohmatin; Fani Firmansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of perceived usability, perceived ease, perceived security, interest, and trustworthiness. The quantitative research methodology used is an explanatory research approach to examine the influence of perceived usability, perceived convenience, and perceived security on the interest of Generation Z in using Islamic mobile banking with trust as a mediation variable. The population of this study consisted of students in Malang City who used Islamic mobile banking, and the sample used 100 students who met the criteria using purposive sampling techniques. Data was collected through questionnaires containing statements related to research variables. The results showed that perception, usefulness, and trust significantly affected interest. In comparison, the perception of convenience and security did not significantly affect interest. In addition, trust can mediate the influence of perceived usefulness and safety on interest. However, trust cannot mediate the influence of perceived convenience on interest. This study concludes that these factors can be a reference for banks to make strategies to increase the interest of Islamic mobile banking users.